2003
DOI: 10.1177/0891243202238978
|View full text |Cite
|
Sign up to set email alerts
|

Giving Birth Like A Girl

Abstract: Relational, selfless, caring, polite, nice, and kind are not how we imagine a woman giving birth in U.S. culture. Rather, we picture her as screaming, yelling, self-centered, and demanding drugs or occasionally as numbed and passive from pain-killing medication. Using in-depth interviews with women about their labor and childbirth, the author presents data to suggest that white, middle-class, heterosexual women often worry about being nice, polite, kind, and selfless in their interactions during labor and chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 18 publications
1
100
4
1
Order By: Relevance
“…Physicians are also under pressure to provide perfect outcomes in a world where childbirth has to fit around financial productivity, limited healthcare resources, fear of litigation and rising cost of malpractice insurance (Bergeron, 2007). Research about internal sense of control based on perceptions of gender has indicated that white middle class women worry about being nice, polite, kind, and selfless in their interactions during labor and childbirth (Martin, 2003). Worries about interactions during childbirth for minority women are largely unknown.…”
Section: Societal Prospectivementioning
confidence: 99%
See 3 more Smart Citations
“…Physicians are also under pressure to provide perfect outcomes in a world where childbirth has to fit around financial productivity, limited healthcare resources, fear of litigation and rising cost of malpractice insurance (Bergeron, 2007). Research about internal sense of control based on perceptions of gender has indicated that white middle class women worry about being nice, polite, kind, and selfless in their interactions during labor and childbirth (Martin, 2003). Worries about interactions during childbirth for minority women are largely unknown.…”
Section: Societal Prospectivementioning
confidence: 99%
“…The financial and social pressure to remain employed in today's culture is strong (Martin, 2003). Women move frequently, often far away from extended family and close friends so that the traditional social support for women during pregnancy and childbirth is disappearing.…”
Section: Societal Prospectivementioning
confidence: 99%
See 2 more Smart Citations
“…‫املتوسط‬ ‫لرشق‬ ‫الصحية‬ ‫املجلة‬ ‫العرشون‬ ‫و‬ ‫الثالث‬ ‫املجلد‬ ‫السادس‬ ‫العدد‬ birth process, and women without such support are more fatalistic about their role in the birth process (51). Some research has shown that women who receive social support in pregnancy and during labour have lower rates of caesarean section (52).…”
Section: Bahonar Et Al (2010)mentioning
confidence: 99%